Optimization of β-mannanase production from Bacillus licheniformis TJ-101 using response surface methodology - Liu, Zhao-Hui (Array, 2008)
Summary: Plackett-Burman design, central composite design and response surface analysis were carried out with the aim of optimizing culture conditions for β-mannanase production from Bacillus licheniformis TJ-101. Screening experiments of Plackett-Burman design were firstly employed to evaluate the effects of 16 variables on β-mannanase production. The four identified significant variables, i.e. the mass concentration of Na2HPO4, the mass concentration of KH2PO4, initial pH and medium volume, were further optimized by central composite design and response surface analysis. The optimum values of four critical variables were determined as Na2HPO4 6.4 g/ lL-1, KH2PO4 0.36 g L-1g/l, initial pH 7.7 and medium volume V = 30.1 mlmL. Under these conditions, the β-mannanase activity can experimentally reach a = 523.1±5.9 U/ ml mL-1 (127.7 % increase compared with the enzyme activity before optimization) at the flask level. Moreover, oxygen limitation and initial pH remarkably affected β-mannanase production from Bacillus licheniformis TJ-101 as revealed by response surface analysis. Maximum β-mannanase activity was increased by 73.7 % in a 6.6- l L fermenter using the optimized medium and dissolved oxygen at 20 % saturation